356 Albumin Synthesis Rates in VLBW Infants - Effects of High dose Amino Acid and Lipid Administration from Birth Onwards. (October 2012) - Vlaardingerbroek, H; Rook, D; Schierbeek, H; Akker, CHP van den; Vermeulen, MJ; Goudoever, JB van
Abstract : Introduction: Albumin is one of the most important proteins in plasma and plays a key role in physiological processes like preservation of colloid osmotic pressure and binding of bilirubin and drugs. However, albumin concentrations are often low during the first days of life in preterm infants. We hypothesized that early parenteral lipid and high dose amino acid (AA) administration from birth onwards to very low birth weight (VLBW) infants increases hepatic albumin synthesis rates and albumin concentration. Methods: Inborn VLBW infants were randomized to one of three different parenteral nutritional regimens within 6hrs after birth (Figure 1 ). Lipids were started at 2 g/(kg.d) and increased to 3 g/(kg.d) the following day. At postnatal day 2, infants received a primed continuous infusion of [ 13 C6, 15 N]leucine. Mass spectrometry was used to determine the fractional and absolute albumin synthesis rates (FSR and ASR, respectively). Results: Albumin FSR, concentration, and ASR were not significantly different between groups (Figure 2 ; median, IQR). Conclusion: Albumin concentration was in normal range in all groups. Albumin synthesis rates and concentration are not increased upon introduction of 2g lipids/(kg.d) and 3.6g AA/(kg.d) from birth onwards.